A különleges minőségű élelmiszerek vidékfejlesztésben betöltött szerepe - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
In our work the concept of "special foods" - in a wider sense - is defined as foods not yet widespread in public consumption. They represent special quality, which - in our opinion - may derive from traditions, from geographical properties related to food production or from the organic nature of production. The main characteristics of individual groups of special foods (foods originating from organic production, geographical indications products, traditional and local foods) are reviewed and proposals are made for improving the quality of life and for increasing the population-retaining capacity in rural regions. Special foods represent a higher added value, their production offers a possibility for inhabitants in rural areas to make agricultural production more diverse, to popularize the products of disadvantaged regions and to increase the farmers’ income.